PERAN PESANTREN DALAM MEMBENTUK KARAKTER DIERA GLOBALISASI - Astika, Lusi; Nur Evisa, Siti; Chanifudin (LPPM STAI Muhammadiyah Probolinggo, 2024)
This journal explains the role of Islamic boarding schools in educating a person's character in the era of globalization. The research used is a literature review type of research. In this research, Islamic boarding schools are able to play a role in shaping the character of a student (santri) by being supported by the Islamic boarding school environment, namely, a kiai or ustadz and ustadzah. Because this cannot be separated from the role of a teacher as an educator in creating students who have noble character and morals. Islamic boarding schools in character education must act as guardians and also as examples of religious values, educational institutions, and also as institutions for religious education and socio-social education. Islamic boarding schools can also carry out their roles, duties, vision and mission, and functions of Islamic boarding schools as an inspiration and also a motivator for people in their environment and even people in the world, so that someone becomes a better human being who has characteristics of noble character and is beneficial to others.